BEBERAPA KESALAHAN KONSEPTUAL PADA UU CIPTA KERJA MENURUT ILMU HUKUM ADMINISTRASI NEGARA - Muhammad Adiguna Bimasakti (Puslitbang Hukum dan Peradilan bekerja sama dengan Ditjen Badimiltun, 2021)
The promulgation of Law Number 11 Year 2020 Regarding Job Creation Bill by the Indonesian Government that uses the omnibus law model has caused polemics both theoretically and pragmatically. The omnibus law model breaks through the paradigm of law-making that has been known in Indonesia for of its unusual method of regulating many themes in one single bill. In terms of substance, especially in this paper concerning administrative law, many concepts are mixed up so that many things which in theory stray far from the science of State administrative law adopted in Indonesia. Among those that will be discussed in this paper are four problems namely 1.) The constitutionality of omnibus law method in the Law No. 11 of 2020 regarding Job Creation, 2.) The concept of governmental authority in the context of regional and central government relations, 3.) The Tacit Authorization concept, and 4.) The concept of licensing in the broader sense. This paper uses the literature study method, in which the writer observes the problems based on related literatures and regulations. The conclusion that can be drawn in this paper is that this law which regulates those four problems is still had a lot of mistakes and needs to be reviewed by the legislators or by President of the Republic of Indonesia.